2014
DOI: 10.1038/tp.2014.83
|View full text |Cite|
|
Sign up to set email alerts
|

Serotonin tranporter methylation and response to cognitive behaviour therapy in children with anxiety disorders

Abstract: Anxiety disorders that are the most commonly occurring psychiatric disorders in childhood, are associated with a range of social and educational impairments and often continue into adulthood. Cognitive behaviour therapy (CBT) is an effective treatment option for the majority of cases, although up to 35–45% of children do not achieve remission. Recent research suggests that some genetic variants may be associated with a more beneficial response to psychological therapy. Epigenetic mechanisms such as DNA methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
79
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 51 publications
6
79
0
2
Order By: Relevance
“…Another study examining response to intensive dialectical behavior therapy in adults with borderline personality disorder demonstrated differential patterns of BDNF methylation change associated with scores of depression, hopelessness, and impulsivity following treatment 29. Finally, we previously showed that one CpG site upstream of the SERT promoter increased in DNA methylation during the course of therapy in treatment responders, but decreased in nonresponders 27. Intriguingly, in all of these studies responders and nonresponders showed a difference in the direction of DNA methylation change.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Another study examining response to intensive dialectical behavior therapy in adults with borderline personality disorder demonstrated differential patterns of BDNF methylation change associated with scores of depression, hopelessness, and impulsivity following treatment 29. Finally, we previously showed that one CpG site upstream of the SERT promoter increased in DNA methylation during the course of therapy in treatment responders, but decreased in nonresponders 27. Intriguingly, in all of these studies responders and nonresponders showed a difference in the direction of DNA methylation change.…”
Section: Discussionmentioning
confidence: 86%
“…In this study, we find genotype‐dependent changes in methylation during treatment are associated with treatment outcomes at follow‐up . Previous studies investigating both genetic26, 30, 32 and epigenetic26, 27 markers of response to psychological therapy have also demonstrated the largest effects at follow‐up. Future research of predictors and markers of response to psychological therapies would be improved by including this time point.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to being a potential therapeutic target, epigenetic marks could be useful in predicting and also monitoring therapeutic approaches (Guintivano et al, 2014a(Guintivano et al, , 2014bPowell et al, 2013;Roberts et al, 2014;Yehuda et al, 2013). For example, the peripheral blood methylation status at the GR locus that is altered in response to trauma exposure may predict the response to prolonged exposure psychotherapy, as proposed in a small pilot treatment study.…”
Section: Epigenetic Modifications As a Potential Target Of Psychiatrimentioning
confidence: 99%
“…This suggests that epigenetic changes in response to the traumatic event could predict further environmental modification, in this case by psychotherapeutic intervention (Yehuda et al, 2013). Roberts et al observed an increasing DNA methylation at the serotonin transporter locus in individuals with anxiety disorders responding to cognitive behavioral therapy as compared to non-responders, who actually showed a decrease in DNA methylation (Roberts et al, 2014). Moreover, in a recent study by Powell et al, DNA methylation at the IL6 locus predicted response to classical antidepressant treatment in the Genome-Based Therapeutic Drugs for Depression (GENDEP) cohort, suggesting that epigenetic profiling before treatment could be used to reduce the likelihood of treatment failure by selecting the appropriate drug (Powell et al, 2013).…”
Section: Epigenetic Modifications As a Potential Target Of Psychiatrimentioning
confidence: 99%
“…For example, if adversity affects peripheral DNAm of certain genes, which, in turn, reliably increase vulnerability for borderline personality disorder (i.e., high predictive specificity), then an efficacious intervention may also show change in both DNAm of the candidate gene and mental health symptoms for responders versus non-responders (i.e., a potential causal mechanism in symptoms). Although this area of research is in early stages, certain small-scale (proof of concept) interventions have reported joint change in DNAm of candidate genes and symptoms of mental health problems, including borderline personality [28] and anxiety [29]. Large-scale randomized controlled trials are needed to increase scientific rigour and to establish causality.…”
Section: Discussionmentioning
confidence: 99%